Civilizar, regenerar e higienizar : a difusão dos ideais da Pedagogia Moderna por Helvécio de Andrade 1911-1935 - Valença, Cristina de Almeida (2006)
Civilization, regeneration, education of the senses and higienization are the words of order of the new educational movement called Modern Pedagogia witch was inserted in the ideals of the republic. This study has the objective of analising the education at Sergipe in the XX century. The point of view selected for this study was related to the cultural history, especially enphasizing the analitical categories established by Chartier, the appropriation and representation; the concepts of Bourdieu from field, capital and the knowledges of Norbert Elias, to civilize. At Sergipe, education in the beginigs of republic was the target of the modern pedagocic movement wich turn it in a new way of thinking about school pratice and public educational politics. That resulted in a new profile of the institutions wich was now concerned about to civilize. Inspired by those ideas, Helvécio de Andrade, through his actions and publications, looked foward to spread out the new rules of education in the public instruction at Sergipe.